Contribution of Financial Literacy to Behavior - Chaulagain, Ramesh Prasad (Journal of Economics and Behavioral Studies, 2015)
Almost all the people around the world behave with money in daily lives whereas understanding how they behave is important. It is obvious that the education, which can not affect behavior of people, is worthless. Financial literacy also is believed to change financial behavior of individuals. Financial literacy implies two sides, i.e. concept and application of personal finance. The concept consists financial knowledge and basic skill of numeracy and financial decisions; the application consists the financial behavior. The focus of the article is to discuss how the financial literacy contributes financial behavior and thereby financial wellbeing of individuals. For this, the article presents a transmission mechanism of financial knowledge and skill to the financial behavior through a framework. However, there are some contexts, conditions and criterions to transmit the financial knowledge and skill into financial behavior and well-being. Moreover, categorizing the financial behavior of individuals is a significant issue in study of financial literacy. Particularly for the survey research, a new categorization and degree of the financial behavior is presented, which is ranked as good, moderate and weak financial behavior in comparative ways. The study establishes the relevancy of the evaluation criteria of financial behavior and also presents a framework on how the financial educations work contribute in financial behavior.